2021
DOI: 10.1155/2021/1205473
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Diagnosis of Rolling Bearing Fault Based on Improved Convolutional Neural Network and LightGBM

Abstract: Aiming at the problems of weak generalization ability and long training time in most fault diagnosis models based on deep learning, such as support vector machines and random forest algorithms, one intelligent diagnosis method of rolling bearing fault based on the improved convolution neural network and light gradient boosting machine is proposed. At first, the convolution layer is used to extract the features of the original signal. Second, the generalization ability of the model is improved by replacing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…We decided to use GBDT based methods as classifier because of their high prediction accuracy, and adaptability to non-linear characteristics and good training effect [31,49]. XGBoost, CatBoost and LightGBM were chosen as classifier candidates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We decided to use GBDT based methods as classifier because of their high prediction accuracy, and adaptability to non-linear characteristics and good training effect [31,49]. XGBoost, CatBoost and LightGBM were chosen as classifier candidates.…”
Section: Discussionmentioning
confidence: 99%
“…XGBoost, CatBoost and LightGBM were chosen as classifier candidates. XGBoost was chosen because of its new regularization method that resists overfitting, therefore making the model more robust [31,50]. CatBoosts improved generalization as well as its ability to capture high-order dependencies makes it a viable candidate as well [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tian et al [11] proposed an improved genetic algorithm (IGA) combined with the global optimization characteristics of the genetic algorithm (GA) and the local optimal solution of the simulated annealing (SA) algorithm in this paper, which adopts SA in the process of selecting subpopulations. Some scholars have found that the neural network has good performance in feature extraction and damage recognition [12,13].…”
Section: Introductionmentioning
confidence: 99%